Quality of information offered to women by drug sellers providing medical abortion in Nigeria: Evidence from providers and their clients - Akinyemi, Akanni; Owolabi, Onikepe Oluwadamilola; Erinfolami, Temitope; Stillman, Melissa; Bankole, Akinrinola (Frontiers in Global Women's Health, 2022)
Evidence confirmed that the demand for medical abortion (MA) increased significantly during the COVID-19 outbreak in many developing countries including Nigeria. In an abortion-restrictive setting like Nigeria, local pharmacies and proprietary patent medicine vendors (PPMVs) continue to play a major role in the provision of MA including misoprostol. There is a need to understand these providers’ knowledge about the use of misoprostol for abortion and the quality of information they provide to their clients. This study utilized primary data collected from drug sellers (pharmacists and PPMVs) and women across 6 LGAs in Lagos State, Nigeria. The core sample included 126 drug sellers who had sold abortion-inducing drugs and 386 women who procured abortion-inducing drugs from the drug sellers. We calculate quality-of-care indices for the care women received from drug sellers, drawing on WHO guidelines for MA provision. The index based on information from the sellers had two domains - technical competency and information provided to clients, while the index from the women’s perspectives includes an additional domain, client experience. Results show that the majority of drug sellers in the sample, 56% (n = 70), were pharmacists. However, far more than half of women 60% (n = 233) had visited PPMVs. Overall, the total quality score amongst all drug sellers (mean 0.48, SD0.15) was higher than women’s responses (mean 0.39, SD 0.21). Using our quality-of-care index, pharmacies and PPMVs seem to have similar technical competency (mean score of 0.23, SD 0.13 in both groups out of 1), whilst PPMVs performed better on the information provided to client domain (mean score of 0.79, SD 0.17 compared with pharmacies 0.69, SD 0.25). Based on women’s reports, PPMVs scored better on both quality-of-care domains (technical competency and information provided to clients) compared with pharmacies. In resource-constrained settings such as Nigeria, particularly in the context of health emergencies like COVID-19, there is the need to continue to strengthen and engage PPMVs’ capacity and skills in dispensing and administration of MA drugs as a harm reduction strategy. Also, there is the need to target frontline providers in pharmacies for training and skill upscale in MA provision.